2016
DOI: 10.1080/15384101.2016.1231287
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells that survive checkpoint adaptation contain micronuclei that harbor damaged DNA

Abstract: We have examined the relationship between checkpoint adaptation (mitosis with damaged DNA) and micronuclei. Micronuclei in cancer cells are linked to genomic change, and may induce chromothripsis (chromosome shattering). We measured the cytotoxicity of the cancer drug cisplatin in M059K (glioma fibroblasts, IC50 15 mM). Nearly 100% of M059K cells were positive for histone gH2AX staining after 48 h treatment with a cytotoxic concentration of cisplatin. The proportion of micronucleated cells, as confirmed by mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…Investigation of checkpoint adaptation led to the finding that it causes the formation of micronuclei in cells [ 10 , 11 ]. Micronuclei are distinct from the main nucleus and encapsulate full lagging chromosomes or fragments of chromosomes that are not incorporated in the main nucleus after anaphase [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of checkpoint adaptation led to the finding that it causes the formation of micronuclei in cells [ 10 , 11 ]. Micronuclei are distinct from the main nucleus and encapsulate full lagging chromosomes or fragments of chromosomes that are not incorporated in the main nucleus after anaphase [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Micronuclei contribute to genomic instability, and are a characteristic of cancer cells. Cells that undergo checkpoint adaptation show a 50% increase in the number of micronuclei compared with non-treated cancer cells [ 10 , 11 ]. The cells containing micronuclei are able to survive for several cycles, and chromosomes enclosed in these micronuclei could be reunited in the main nucleus of the daughter cells.…”
Section: Introductionmentioning
confidence: 99%
“…The Alu element is commonly found in repetitive regions. Recently, many environmental factors were shown to alter Alu methylation, which could lead to chromosomal instability resulting in chromosomal rearrangements [46]. We found that loci in long repetitive regions were significantly enhanced in DMPs following 15 and 15 + 3 FDIR, demonstrating that also irradiation can induce such alterations.…”
Section: Discussionmentioning
confidence: 59%
“…The process of DNA damage in general and specially in DNA DSB repair are occur in G2 or adaptive checkpoint before the cell entering the mitotic phase. Lewis and Goldstein [24] found that, production of micronuclei were correlated to checkpoint adaptation as part of process that contribute to genomic change. These processes were indicated by high expression of γ-H2AX and 53BP1 foci.…”
Section: Resultsmentioning
confidence: 99%